The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5tb01056j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition to construct a nature inspired multilayer chitosan/layered double hydroxides hybrid gel for stimuli responsive release of protein

Abstract: 7In this study, we report a single electrodeposition process to fabricate multilayered 8 chitosan/layered double hydroxides (LDHs) hybrid hydrogel for stimuli responsive protein release. 9LDHs nanoplatelets with regular hexagonal shape were synthesized by hydrothermal method and 10 a model protein, insulin, was adsorbed to the surface of LDHs (INS-LDHs) caused by electrostatic 11 interactions. The insulin loading ratio could reach 20% (w/w) and the INS-LDHs were 12 characterized by energy dispersive spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 40 publications
0
23
0
1
Order By: Relevance
“…Numerous investigations have shown that coating of alginate microspheres with chitosan layer is and effective way of an active agent controlled release as a desirable characteristic for all delivery systems (Li et al, 2014;Lucinda-Silva, Salgado, & Evangelista, 2010;Wang & Zhao, 2013). Layering technology has been often utilized for producing novel materials with tailorable properties, such as, for example, multilayered chitosan/layered double hydroxides hybrid hydrogel as a promising controlled delivery system (Zhao et al, 2015(Zhao et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigations have shown that coating of alginate microspheres with chitosan layer is and effective way of an active agent controlled release as a desirable characteristic for all delivery systems (Li et al, 2014;Lucinda-Silva, Salgado, & Evangelista, 2010;Wang & Zhao, 2013). Layering technology has been often utilized for producing novel materials with tailorable properties, such as, for example, multilayered chitosan/layered double hydroxides hybrid hydrogel as a promising controlled delivery system (Zhao et al, 2015(Zhao et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore expected that a daidzein-loaded microsphere coating system will possess the potential to stimulate bone related cells for enhanced osseointegration. Taking advantage of the controllable drug release performance from PHBV microspheres 18 and the simplicity of the electrophoretic deposition (EPD) technique to produce polymer coatings on metallic substrates, 19,20 PHBV microspheres were able to be stabilized into a polymer coating, and a minimized and prolonged drug release rate could be expected. Combination of PHBV microspheres and biopolymers was investigated by EPD at first.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, insulin was loaded on LDH according to the method of Zhao et al [23]. A chitosan solution that comprised 8 mg of chitosan, 4 mL of an aqueous solution of acetic acid (1% v/v) and NaOH at pH 6.5 was prepared.…”
Section: Preparation Of Novel Ldh-ins-csnpsmentioning
confidence: 99%